Pengaruh Terapi Pijat Terhadap Kenaikan Berat Badan Bayi Prematur di RSUP. Dr. M. Djamil Padang: Effect of Massage Therapy on Weight Gain Premature Infants at the Hospita Dr. M. Djamil Padang - Yori Rahmi; Wedya Wahyu; Eliza Anas (Fakultas Keperawatan Universitas Andalas, 2012)
Prematurity had a very high risk in mortality of infants. An infant born with a pregnancy period of less than 37 weeks and with a body weight corresponding to the gestation period is referred to as a premature or less months neonate. Premature infants often experience low body weight problems. Stimulation is needed to raise the body weight of premature infants. One of the non-invasive actions that encourage weight gain is massage therapy. According to the American Association of Massage Therapy (AMTA), massage is defined as the manipulation of soft tissue using hands or body to hold, move, or apply stress manually. The research focused on knowing the influence of massage therapy on the body weight of premature infants in Dr. M. Djamil Padang. The study was conducted from March to April 2012 on 18 stable premature infants. This research used a pre-experimental one-group pretest-posttest measurement. It was done by recording the body weight of the infants before and after massage therapy was applied for 5 days. A dependent T-Test (paired t-test) was used for statistical analysis. The statistical test results with bivariate analysis showed that there was a significant change in body weight (p = 0.000). This indicates that massage therapy significantly affects the increase in the body weight of premature infants.